Aquaculture Base Group (ABG) as an Effort to Develop a Sustainable Fisheries Economy - Syavin Pristiwayuning Rachmadhany; Rusdi Abdat; Ahmad Rido'I Yuda Prayogi (Journal of Aquaculture Science, 2021)
Indonesia has enormous potential in the field of fisheries, this is because about 70% of its territory is oceans and archipelagic countries. Shrimp farming in Indonesia is a practice that is widely practiced by Indonesians. This is because shrimp is a fishery commodity that has the highest demand. Aquaculture Base Group (ABG) aims to manage communities, who were originally individuals in managing ponds to become groups, because it will make it easier to get support from the government and get more benefits than only individuals. The program is implemented using several methods, namely socializing the importance of cultivation using the ABG method, explaining the advantages of using the ABG method, forming cadres for coordination between extension agents and the community so that communication can be evenly distributed, and distribution for each pond and job desk. As well as the holding of monitoring and evaluation, whether to get more efficient results when using ABG or individual methods. The ABG method is more efficient than using the individual method, including fry and feed can be purchased at a lower price, fry can be done together so that supervision will be easier, management of water sources is more maintained, and biosecurity is easier, and the impact of management be the responsibility of groups not individuals. Conclusion: the use of ABG cultivation method is more efficient, get affordable prices when buying fry and feed, disease management that can be managed together, cheaper electricity, easier biosecurity and more maintained water management (Tandon and Waste Water Treatment Plant) . Keyword : Fishery, shrimp farming, group, sustainable